Drying Carnation Flowers by Using Desiccantas - , Shivkumar Mahadeo Wararkar, SR Dalal, Shiva Nand Mohan Mishra, Vikas Singh Senger (Archives of Current Research International, 2025)
The objective of the experiment was to evaluate the dehydration techniques, suitable desiccant and suitable drying temperature for carnation flower. The experiment was conducted in the Laboratory, Department of Horticulture, Dr. Panjabrao Deshmukh Krishi Vidyapeeth, Akola during the years 2015-16 and 2016-17. The objective was to determine the most suitable desicants for drying carnation flower. The study followed a Randomized Block Design with a four replication. Six different drying methods were tested as treatments: Air drying in the shade (control), drying after embedding in borax, clean fine sand, silica gel, a 1:1 glycerol-water mixture, and a 1:3 glycerol-water mixture. Maximum weight of dry flower 4.23, 4.13 and 4.18 g was found in 1:1 glycerol: water solution embedding. Maximum diameter of dry flower 5.13, 5.23 and 5.18 cm was recorded in sand embedding drying. Maximum moisture loss 75.14, 74.44 and 74.79 % was observed when flowers embedded in silica gel. Minimum moisture content 56.98, 53.14 and 55.06% was observed in 1:1 glycerol: water solution embeddingless time 3.68, 3.53 and 3.60 days was required for drying of carnation flowers in silica gel, when compared with flowers dried in air drying 13.55, 13.13, and 13.34 days. Maximum reduction in diameter of flower 0.77, 0.97 and 0.87 cm was recorded when flowers embedded in treatment silica gel.